2019
DOI: 10.1021/acsami.9b06302
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoresponsive Behavior of a Polymer-Embedded Red-Light Emitting Rotaxane Mechanophore

Abstract: A red-light-emitting photoluminescent supramolecular mechanophore based on an interlocked molecular motif is presented. The rotaxane-based mechanophore contains a cyclic compound featuring a π-extended 4,4-difluoro-4bora-3a,4a-diaza-s-indacene (BODIPY) dye as a red emitter that was threaded onto a dumbbell-shaped molecule containing an electron-poor 1,4,5,8-naphthalenetetracarboxylic diimide quencher at its center. Through two aliphatic hydroxyl groups attached to the dumbbell and the cycle, the mechanophore w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 42 publications
7
80
0
Order By: Relevance
“…[ 149 ] Further exploring their utility, polymers were prepared in which the dye separation in the pristine, rotaxane‐bearing PU leads to a trapped state. [ 150 ] Thus, a cyclophane‐based macrocycle was threaded onto a dumbbell with a BODIPY dye to furnish a red‐light emitting rotaxane. Covalently embedding the latter into a PU matrix caused the rotaxane to remain in a trapped state in which the fluorophore and quencher moieties were separated.…”
Section: Mechanical Stimulation Of Hetero‐molecular Complexesmentioning
confidence: 99%
“…[ 149 ] Further exploring their utility, polymers were prepared in which the dye separation in the pristine, rotaxane‐bearing PU leads to a trapped state. [ 150 ] Thus, a cyclophane‐based macrocycle was threaded onto a dumbbell with a BODIPY dye to furnish a red‐light emitting rotaxane. Covalently embedding the latter into a PU matrix caused the rotaxane to remain in a trapped state in which the fluorophore and quencher moieties were separated.…”
Section: Mechanical Stimulation Of Hetero‐molecular Complexesmentioning
confidence: 99%
“…However, the exact force acting on a mechanophore is difficult to ascertain, as many factors during cavitation or within a material influence the transmittance of the force to the mechanophore, such as the molecules overall rigidity, [3f,9] the length of attached residues [10] or the material's morphology [11] . Thus, recent activities on metallocenes, [7] Cu‐pyridine, [12] and B−N bonds [13] demonstrated metal/ligand‐cleavage in polymeric bulk‐systems or in solution, which finally did not allow for a precise, direct quantification of the individual metal/ligand‐bond upon mechanical stressing.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Among these, particularly attractive are mechanophores that do not require scission of covalent bonds for the activation and change of their properties. [29][30][31][32][33] In the case of rotaxanes, the activation process does not involve any bond cleavage, leading to a low activation energy of the process. [30] In the study reported herein, we extensively investigated the vase-kite switching of tetraquinoxaline cavitands in polymers through the application of tensile strain.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, thanks to the progress in mechanophore design, a broad range of mechanically‐triggered transformations was attained . Among these, particularly attractive are mechanophores that do not require scission of covalent bonds for the activation and change of their properties . In the case of rotaxanes, the activation process does not involve any bond cleavage, leading to a low activation energy of the process …”
Section: Introductionmentioning
confidence: 99%